Retrospective analysis of treatment outcomes following reirradiation in locoregionally recurrent head and neck cancer patients: A single institutional study. Issue 2 (17th August 2014) - Kakria, Anjali; Rawat, Sheh; Bhutani, Ritu; Gupta, Gourav; Devnani, Bharti; Wahi, Inderjeet K; Ahlawat, Parveen
Abstract Aim To present a retrospective analysis of treatment outcomes following reirradiation in locoregionally recurrent head and neck cancer patients at our institute. Methods Thirty‐one patients of head and neck cancer who presented with a locoregional recurrence from April 2007 to April 2012 underwent salvage reirradiation. Median dose of first‐time radiation was 70 Gy. Median duration of gap between the first and second course of radiation was 45.6 months. The median dose of reirradiation was 60 Gy. Conformal radiotherapy technique in the form of intensity modulated radiotherapy was used in 60% (17) of patients. Fourteen patients received concurrent chemotherapy or immunotherapy. Results After a median follow‐up of 20.6 months, 12 patients were alive with no evidence of disease. The 3‐year disease‐free survival and overall survival were 28.7 and 48.5%, respectively. Acute and late toxicities were reported in 29 and 61% of patients, respectively. Severe grade 3 and 4 late complications were observed in nine patients but none of them led to mortality. Conclusion Reirradiation appears to be both feasible and well tolerated in patients treated with previous radiotherapy for recurrent and second primary head and neck cancer. Careful case selection for reirradiation based on patient's performance status and tumor characteristics is essential.